Species delimitation and taxonomic revision of Oxyopes (Araneae: Oxyopidae) of Taiwan, with description of two new species - Lo, Ying-Yuan; Cheng, Ren-Chung; Lin, Chung-Ping (Zootaxa, 2021)
This study revised the spider genus Oxyopes Latreille, 1804 in Taiwan and delineated the species boundaries based on morphological and molecular characters. A total of seven Oxyopes spiders were recognized, including two newly described species, O. hasta sp. nov. and O. taiwanensis sp. nov. Oxyopes fujianicus Song & Zhu 1993 from Yilan County, Nantou County, and Kaohsuing City, and O. striagatus Song 1999 from New Taipei City, Taichung City, Nantou County, and Kaohsiung City were recorded for the first time in Taiwan. An identification key and a distributional map of Taiwanese Oxyopes species were provided. Partial COI sequences were obtained for molecular phylogenetic and species delimitation analyses. Maximum likelihood and Bayesian phylogenies, and DNA barcoding gap analysis supported morphologically defined species. However, molecular species delimitation based on Automatic Barcode Gap Discovery (ABGD), PID (Liberal), and generalized mixed Yule coalescent (GMYC) were incongruent in species assignment. The results showed that the interspecific genetic divergence between O. sertatus and O. taiwanensis was relatively low (1.28 ± 0.43%), and the intraspecific genetic divergence of O. striagatus was relatively high (1.69 ± 0.35%). Ecological data, additional samples and genetic loci are required to further examine the level of reproductive isolation and patterns of population genetic structure in Taiwanese Oxyopes.